FROM THE HISTORY OF THE STUDY OF LATE PALEOLITHIC SITES - N. Abduvalieva (Sciental Journals Publishing, 2025)
The article analyzes the history of the study of the Late Paleolithic period in Central Asia, which began in the 1960s-70s of the 20th century, focusing on the study of sites such as Obirakhmat, Kulbulak, Samarkand, Siyobcha, Shugnov, Khojagor, and Yangaja 2.
Keywords: Late Paleolithic, Neolithic, stone tools, Obirakhmat, Kulbulak, Samarkand, Siyobcha, Shugnov, Khojagor, Yangaja 2.